(untitled) (TSUL LEGAL REPORT, 2026)
The article analyzes the legal basis of cooperation between mass media and citizens’ self-government bodies in the implementation of public control. In the developed countries of the world, effective cooperation between civil society institutions and the state is very relevant as a form of cooperation that solves social and economic problems. In this regard, the effectiveness of the state power apparatus, formed with the help of democratic procedures, is related to the presence of public control over the activities of state bodies, which is carried out by civil society institutions. Today, public control is considered not as a means of pressure on the authorities but as a method of harmonious communication between civil society and the state and is one of the main factors that serve to eliminate social tension in society